ESTUDO DO EQUILÍBRIO RADIOATIVO DAS SÉRIES DO 238U E 232Th EM ROCHAS VULCÂNICAS DAS ILHAS DA TRINDADE E DE MARTIN VAZ - Santos, R. N. dos; Marques, L. S.; Brenha-Ribeiro, F. (Geochimica Brasiliensis, 2011)